Initial investigation on the needs of laboratory in microelectronic subject / Nur Syahirah Kamarozaman, Norhidayatul Hikmee Mahzan and Shaiful Bakhtiar Hashim - Kamarozaman, Nur Syahirah; Mahzan, Norhidayatul Hikmee; Hashim, Shaiful Bakhtiar (2018)
Measuring students' academic performance has received quite considerable attention till today. This study was conducted to evaluate the significance of laboratory practice in "Fabrication Process" as one way of better apprehensive toward theoretical knowledge. The study population was the second last year students whom enrolled in microelectronic course. A questionnaire based on student's perception towards this topic was collected and analyzed. Based on the findings, laboratory practice may improve student's knowledge level thus bettering their apprehension ability making it more relatable to the industry. From this initial investigation, it can be said that majority of the students agree on the needs of laboratory practice in order to improve their understanding about this course.